Hypertensive disorders in pregnancy : a 5-year analysis of the wartime and postwar period in south-western region of Bosnia and Herzegovina - Tomić, Vajdana (Array, 2009)
Summary: Hypertensive disorders are among the most common complications in pregnancy and a major cause of perinatal morbidity and mortality. The aim of this study was to investigate the risk factors and adverse perinatal outcomes of pregnancies in mothers with hypertensive disorders, as well as the adequacy of prenatal care during the wartime and postwar period in South-Western region of Bosnia and Herzegovina. This study included a total of 542 pregnancies with hypertensive disorders during 5-year study period (1995–1999) and 1559 randomly selected controls. Data on risk factors, adverse perinatal outcomes (for singleton pregnancies only) and prenatal care on pregnant women were extracted from the medical records and compared with controls. Chi-square test and crude odds ratio (OR) with 95% confidence interval (95% CI) were used in statistical analysis. The average five-year incidence of hypertensive pregnancy disorders was 6.5% and it was significantly higher in 1995, the last year of the war, than in the postwar period (1996–1999) (p=0.02). Factors significantly associated with hypertensive pregnancy disorders were maternal age >34, nulliparity, multifetal gestation and male newborn (p<0.001; except p=0.002 for male newborn). Severe forms of hypertensive disorders were significantly associated with adverse perinatal outcomes: preterm birth (OR 2.6, 95% CI 1.08–6.3), cesarean delivery (OR 9.2, 95% CI 5.4–15.6), fetal growth restriction (OR 63.8, 95% CI 34.8–117.0), and stillbirth (OR 5.5, 95% CI 2.1–14.1). Women with hypertensive pregnancy disorders had significantly lower number of prenatal care visits than controls (p<0.001). There was a high proportion of normally formed macerated stillbirths in the study (27 out of 30 or 90%) and in the control group (10 out of 12 or 83%). In conclusion, severity of the disorder and adequacy of prenatal care are strongly associated with adverse perinatal outcome related to hypertensive pregnancy disorders